UNDERSTANDING EXPERT OPINIONS ABOUT HALAL PRODUCT LABELS IN BUSINESS PRACTICE (ANALYSIS OF INTERNATIONAL ECONOMIC STUDIES) - Gunawan Widjaja (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2021)
This paper examines several economic business science literature papers related to halal labels in global business practices by studying several papers published in many well-known publications such as Emerald, Sagepub, Google Books, and Taylor & France. We obtained data through online searches, considering that this study was conducted during the implementation of the mass restriction policy to respond to the termination of the Covid-19 chain. Next, we examine the data by involving systems, coding, and evaluation. Before concluding, an in-depth interpretation is carried out so that the data findings correctly answer the problem. So we can conclude that the problem of halal labeling in business practice is that halal label certification is an issue that ensures the features and quality of a product that is recommended by Islamic rules through the Council of Ulama or Islamic scholars who allow the use of the Halal label. It is mainly applied to meat and other products such as milk, canned food, cosmetics, snack, and additives.